Priority information themes for ACP agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The seminar objectives were to discuss priority themes for agricultural information in ACP countries with CTA's partner organisations and to establish a consultation process between CTA and these organisations for selecting appropriate themes...